Variação do fluxo da artéria oftálmica demonstrada ao Ecodoppler após bloqueio peribulbar com (e sem) uso de vasoconstritor em pacientes com catarata - Ilma Patricia Machado (2018)
Ocular blocks are widely used in ophthalmologic surgeries and are related to change in ocular fl. Objective: to evaluate ocular flow by echo-Doppler before and after a peribulbar block (PBB) with lidocaine with and without a vasoconstrictor in patients eligible for cataract surgery. Methods: Fifty-six patients who had an American Society of Anesthesiologists (ASA) classification of I, II, or III and were eligible for cataract phacoemulsification surgery were selected. Patients with other eye diseases were excluded. The patients were divided into two groups: group 1: PBB with 1/200,000 adrenaline; group 2: PBB without adrenaline. Peak systolic velocity (PSV), end -diastolic velocity (EDV) and the resistance index (RI) were evaluated using echo-Doppler before and 10 minutes after a PBB. Results: Before the PBB, there were no differences between groups in regards to the RI, PSV, EDV, presence of hypertension, age or sex. After the PBB, we observed a decrease in the RI in group 1 (p =0,038) .Conclusion: We observed a decrease in the RI in the ophthalmic artery after a PBB with a vasoconstrictor. Other studies are needed to demonstrate the real benefits of adrenaline in peribulabr block.